2005
DOI: 10.1113/jphysiol.2004.064683
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of body fluids and angiotensin II receptors in a rat model of intra‐uterine growth restriction

Abstract: We previously reported that sodium restriction during pregnancy reduces plasma volume expansion and promotes intra-uterine growth restriction (IUGR) in rats while it activates the renin-angiotensin-aldosterone system (RAAS). In the present study, we proceeded to determine whether expression of the two angiotensin II (ANGII) receptor subtypes (AT 1 and AT 2 ) change in relation to maternal water-electrolyte homeostasis and fetal growth. To this end, pregnant (gestation day 15) and non-pregnant Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 56 publications
1
19
0
6
Order By: Relevance
“…In our laboratory, an animal model of impaired foetal growth was developed by administering a low-sodium diet to rats during the last week of gestation (Roy-Clavel et al 1999), inducing an important activation of the maternal reninangiotensin-aldosterone system (RAAS) in comparison to normal pregnant rats (Bedard et al 2005). We recently showed that AT 1 R and P450aldo mRNA expression was enhanced in intrauterine growth restriction (IUGR) foetal adrenal glands and was associated with an increase in serum aldosterone levels (Bibeau et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, an animal model of impaired foetal growth was developed by administering a low-sodium diet to rats during the last week of gestation (Roy-Clavel et al 1999), inducing an important activation of the maternal reninangiotensin-aldosterone system (RAAS) in comparison to normal pregnant rats (Bedard et al 2005). We recently showed that AT 1 R and P450aldo mRNA expression was enhanced in intrauterine growth restriction (IUGR) foetal adrenal glands and was associated with an increase in serum aldosterone levels (Bibeau et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Failure of this adaptation is associated with maternal morbidity/mortality and intrauterine growth restriction (3,27). Despite the progressive PVE, there is no increase in maternal blood pressure due to a marked decrease in total peripheral vascular resistance (2,7).…”
mentioning
confidence: 99%
“…In women, plasma volume (PV) expands ϳ40% and is necessary for perfusion of the growing uterus, placenta, and fetus (4). Inadequate volume expansion is associated with pregnancies compromised by fetal growth restriction (3,31). Furthermore, prevention of PVE through restriction of either sodium or water intake during late pregnancy in the rat results in growthrestricted pups (28,30).…”
mentioning
confidence: 99%